Integrating Halal Assurance and Quality Management: A Strategic Framework for Sustainable Growth in the Food Industry - Hidayati, Luki; Sucipto, Sucipto; Juliana, Juliana; Cheumar, Muhammadtahir (Department of Agro-industrial Technology, University of Brawijaya, 2024)
AbstractThe rising demand for halal-certified food products necessitates a robust assurance system that ensures compliance with religious standards while maintaining food quality and safety. Integrating the Halal Assurance System (HAS) with the Quality Management System (QMS) enhances efficiency but faces challenges such as certification discrepancies, operational constraints, and regulatory complexities. This study employs a systematic literature review using the PRISMA framework, analyzing journals from Scopus, ScienceDirect, and Web of Science. Findings indicate that differences in halal certification standards, including JAKIM (Malaysia), BPJPH (Indonesia), and GSO (Gulf), hinder HAS-QMS harmonization. Small and medium-sized enterprises (SMEs) struggle with implementation due to resource limitations and insufficient training. Technologies like blockchain and the Internet of Things (IoT) improve supply chain transparency and audit efficiency. This study emphasizes integrating halal standards with risk-based quality management, regulatory harmonization, and technological advancements to enhance HAS-QMS adoption. The implications of the research can be utilized by regulators, industry, and academics in designing more effective policies and strategies to implement the integration of halal assurance systems and quality management systems.Keywords: halal assurance system, halal certification, quality management system, risk management, system integration AbstrakPeningkatan permintaan produk pangan bersertifikat halal menuntut sistem jaminan yang memastikan kepatuhan terhadap standar keagamaan serta kualitas dan keamanan pangan. Integrasi Sistem Jaminan Halal (SJH) dengan Sistem Manajemen Mutu (SMM) meningkatkan efisiensi industri pangan tetapi menghadapi tantangan seperti perbedaan standar sertifikasi, kendala operasional, dan kompleksitas regulasi. Studi ini menggunakan metode systematic literature review dengan kerangka PRISMA untuk menganalisis literatur dari jurnal bereputasi yang terindeks di Scopus, ScienceDirect, dan Web of Science. Hasil studi mengidentifikasi bahwa perbedaan standar halal di berbagai negara, seperti JAKIM (Malaysia), BPJPH (Indonesia), dan GSO (Gulf), menjadi hambatan utama dalam harmonisasi SJH-SMM. Usaha kecil dan menengah (UKM) mengalami kesulitan dalam implementasi akibat keterbatasan sumber daya dan pelatihan. Adopsi teknologi seperti blockchain dan Internet of Things (IoT) dapat meningkatkan transparansi rantai pasok halal serta efektivitas sistem audit. Studi ini menekankan pentingnya integrasi standar halal dengan manajemen mutu berbasis risiko, harmonisasi regulasi, dukungan teknologi, dan peningkatan kapasitas industri untuk mempercepat adopsi SJH-SMM. Implikasi hasil penelitian dapat dimanfaatkan oleh regulator, industri, dan akademisi dalam merancang kebijakan serta strategi yang lebih efektif untuk mengimplementasikan integrasi sistem jaminan halal dan sistem manajemen mutu.Kata kunci: integrasi sistem, manajemen risiko, sertifikasi halal, sistem jaminan halal, sistem manajemen mutu